High temperature X-ray diffraction study of the U4O9 formation on UO2 sintered plates - Teixeira, Silvio Rainho [UNESP]; Imakuma, Kengo (Elsevier, 1991)
The surface oxidation of UO2 sintered plates at 170-275 ° C was studied in situ by high temperature X-ray diffractometry. At very low oxygen concentration, UO2 is oxidized to U4O9, while at 300°C and argon-20 vol% oxygen it is oxidized up to U3O7. X-ray diffraction profiles of the UO2, U4O9 and U3O7 phases were well characterized during the transformations. The activation energy for the transformation of UO2 to U4O9, obtained from X-ray diffraction data, was found to be 117 ± 9 kJ/mol and 90 ± 14 kJ/mol for the β-(311) and α-(200) reflections, respectively. © 1991.
Keywords: Chemical Reactions--Radiation Effects; X-rays--Diffraction; Activation Energy; Sintered Plates; Uranium Dioxide